Post-injection syndrome and olanzapine long-acting injection in patients with schizophrenia: A case series - Saheli Dey; Khasnobis, Madhurima (Asian Journal of Medical Sciences, 2022)
Pamoate salt of atypical antipsychotic Olanzapine in long-acting injection depot formulation (OLAI) is often used in patients with schizophrenia having poor compliance. This depots formulation having a cluster of adverse events characterized by post-injection delirium/sedation syndrome (PDSS). Here, we present three cases of different age group, different gender suffering from Schizophrenia of varied duration of illness who developed PDSS after receiving OLAI, how they were identified and promptly managed with early intervention. PDSS noted in approximately 0.07% of the injections, in 1.3% of patients. Symptoms such as sedation, delirium, extrapyramidal symptoms, ataxia, autonomic dysfunction, aggression, and speech impairment were reported, onset was immediate to 3–5 h post-injection, patients recovered within 2–72 h. No such risk factors could be identified in any of the cases. PDSS following OLAI occurs when there is accidental intravascular release of high dose of olanzapine. The importance of post-injection syndrome in the above cases lies in the fact that following administration of OLAI a 3–4-h observation period in a health-care facility in the presence of an appropriate qualified personnel is of utmost importance. Furthermore, one should rule out other causes of acute sedation in such patients before establishing the diagnosis of PDSS. There is no specific antidote for olanzapine and almost all such patients improve with conservative and supportive treatment.